PROJETO DE EDUCAÇÃO AMBIENTAL NO ENSINO FUNDAMENTAL: ESTUDO DE CASO EM UMA ESCOLA DO MUNICÍPIO DE PONTA GROSSA-PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This study is part of the research line Teaching and Learning in the Education Post-Graduation Program – PPGE/UEPG-PR. The study comprises Environmental Education as a project in a public school from the 6th to the 9th years of elementary school in Ponta Grossa – PR. In this sense, thinking Environmental Education as a project creates the possibility of acting in multiple spaces of the society, from the informal to the formal education, as it happens in schools, so that fundamental values are built towards citizenship and environmental ethics. Thus, this study aimed to reveal existing articulations between theoretical foundations of the Political-Pedagogical Project and the Environmental Education project regarding the pedagogical practice of teachers involved in such project at the school. A qualitative approach was chosen through a single case study. The case study was a public school of the city of Ponta Grossa, which develops an Environmental Education project since the year 2005. Data was collected through interviews with six teachers and two principals involved in the project, besides observation and documental analysis. Through the content Analysis (BARDIN, 1977), the following categories were identified: Conceptual relation between environment and Environmental Education; Teaching pedagogical practice and Environmental Education; Project theoretical-methodological basis and its closeness or distancing from the Political-Pedagogical Project and the Environmental Education project. From the interviews, seven approaches to the environment were identified: as resource, system, nature, way of life, problem, object of values, and socio-environmental issue. The Political-Pedagogical Project and the Environmental Education project are based on a critical education, as it is seen in the Environmental Education presented by the interviewees focused perspective of education for citizenship and formation of values. There is not an only conception of the project, being interpreted with multiple views and there is no consensus among teachers on the phases that should compose a project. Predominantly, the limits appointed to carry out an Environmental Education project are related to the problems of the educational system, which reflects the working conditions of teachers, stressing that such gaps do not refer to a single school reality, but is characterized as a problem nationwide.
Environmental Education Project in elementary school: case study in a school in Ponta Grossa
Keywords: projetos; educação ambiental; escola; Ensino Fundamental; projects; environmental education; school; Elementary School; CNPQ::CIENCIAS HUMANAS::EDUCACAO